Effects of Hydroxylated Lecithin on Growth Performance, Serum Enzyme Activity, Hormone Levels Related to Lipid Metabolism and Meat Quality in Jiangnan White Goslings - Wu, Hongzhi; Wang, Sibo; Tian, Yong; Zhou, Ning; Wu, Chunqin; Li, Ruiqing; Xu, Wenwu; Xu, Tieshan; Gu, Lihong; Ji, Fengjie; Xu, Li; Lu, Lizhi (Frontiers in Veterinary Science, 2022)
The objective of the present study was to evaluate the effects of hydroxylated lecithin on growth performance, serum enzyme activity, hormone levels related to lipid metabolism and meat quality in Jiangnan White goslings. 600 1-day-old goslings were randomly divided into five treatments with six replicates and twenty for each replicate. The control group (CG) was fed the basal diet, while the experimental group was fed the basal diet with 50, 100, 200 mg/kg hydroxylated lecithin and 100 mg/kg soy lecithin (HLG50, HLG100, HLG200 and LG100, respectively) in the form of powder. Feed and water were provided ad libitum for 32 days. Compared with the CG, a) the average daily feed intake was higher (P < 0.05) in HLG100, the final body weight and average daily gain were higher (P < 0.05), and the feed conversion ratio was lower in the HLG200; b) the alanine aminotransferase, malate dehydrogenase, leptin, glucagon, thyroid hormone, Triiodothyronine contents in the HLG200 were lower (P < 0.05); c) The breast muscle water holding capacity was higher (P < 0.05) in groups with hydroxylated lecithin, the breast muscle shear force and fibre diameter were lower (P < 0.05) in the HLG100; d) the inositic acid, intramuscular fat, phospholipid contents were higher (P < 0.05), the triglyceride content was lower (P < 0.05) in HLG100 of the breast muscle; e) the relative expression of sterol regulatory element-binding protein-1 genes were higher (P < 0.05) in the treated groups of muscles, the phosphorylase kinase gamma subunit 1 gene expression was shown an opposite trend. In comparison with LG100, a) the feed conversion ratio was lower (P < 0.05) in HLG200; b) the alanine aminotransferase and adiponectin contents were higher (P < 0.05), the malondialdehyde and free fatty acid contents were lower (P < 0.05) in HLG200; c) the water holding capacity and intramuscular fat contents in the breast and leg muscles were higher (P < 0.05) in HLG200. The hydroxylated lecithin concentration of 200 mg/kg improved the growth performance, serum enzyme activity, hormone levels related to lipid metabolism, and the meat quality of Jiangnan White goslings.